Will human population growth and land-use change control tsetse during our life times? - Reid, Robin S.; Kruska, Russell L.; Thornton, Philip K. (OAU/STRC, 1999)
For at least five decades, tsetse biologists have observed that the populations of some species of tsetse (particularly species in the morsitans group of flies) decline as fly habitat is converted into cultivated land and host populations are decimated by hunting. Some have even suggested that tsetse control is unnecessary because human population growth and concomitant land-use change will eventually control the fly, even if no formal tsetse control is attempted. We tested this hypothesis for the African continent by first surveying the literature and establishing the levels of human population density at which populations of the three groups of tsetse flies (morsitans, palpalis and fusca) being to decline and then disappear altogether. We then developed four human population scenarios showing likely levels of human population in the years, 1960, 1990, 2020 and 2040. These data layers were then overlaid with the distribution of each group of tsetse fly and areas of possible tsetse decline were identified. The resulting maps show that large areas of Africa will still have low human populations and thus intact tsetse habitat even 40 years from Africa will still have low human populations and thus intact tsetse habitat even 40 years from today. However, most people and livestock will inhabit areas of high human population density, where it is likely that morsitans populations will have diminished. In these areas, other tsetse species in the palpalis group that are less affected by human population density, such as Glossina palpalis, G. tachinoides and G. fuscipes, will likely be the primary disease vectors. Thus, while it is certain that trypanosomosis will not disappear as a result of human population growth during our lifetimes, the epidemiological nature and the location of the problem will shift.